Energy democracies for sustainable futures - Nadesan, Majia Holmer, 1965-; Pasqualetti, Martin J., 1945-; Keahey, Jennifer; Sovacool, Benjamin K. (Elsevier Academic Press, 2023)
Energy Democracies for Sustainable Futures explores how our dominant carbon and nuclear energy assemblages shape conceptions of participation, risk, and in/securities, and how they might be reengineered to deliver justice and democratic participation in transitioning energy systems. Chapters assess the economies, geographies and politics of current and future energy landscapes, exposing how dominant assemblages (composed of technologies, strategies, knowledge and authorities) change our understanding of security and risk, and how they these shared understandings are often enacted uncritically in policy. Contributors address integral relationships across the production and government of material and human energies and the opportunities for sustainable and democratic governance. In addition, the book explores how interest groups advance idealized energy futures and energy imaginaries. The work delves into the role that states, market organizations and civil society play in envisioned energy change. It assesses how risks and security are formulated in relation to economics, politics, ecology, and human health. It concludes by integrating the relationships between alternative energies and governance strategies, including issues of centralization and decentralization, suggesting approaches to engineer democracy into decision-making about energy assemblages.